P827 Prevalence of viral hepatitis in patients with IBD: A multi-centre and population-based study. (16th January 2018) - Badia, E; Barrio, J; Fernández-Salazar, L; Fuentes, A; Hontoria, G; Sicilia, B; ,
Abstract: Background: There is limited information about prevalence of hepatitis B (HBV) and C virus (HCV) infection in inflammatory bowel disease (IBD). This knowledge is relevant because the viruses may be reactivated under immunosuppressive therapy. The aim of our study is to assess the prevalence of HBV and HCV infection in IBD patients of a population-based area of 4 different hospitals in Castilla y Leon and to evaluate associated risk factors. Methods: A descriptive, observational, retrospective and multicenter study including 4 hospitals in Castilla y León was conducted to analyse HBV and HCV status data of IBD patients and compare that status to some associated risk factors such age, immunosuppressive treatment or disease characteristics. Results: We have included 1277 patients with IBD (702 ulcerative colitis, 548 Crohn's disease and 27 indeterminate colitis). Present and/or past HBV was found in 5.9% of patients of both ulcerative colitis (UC) and Crohn's disease (CD) (UC: HBsAg 0.3%, anti-HBc 5.4%; CD: HBsAg 0.2%, anti-HBc 6.4%). Effective vaccination (anti-HBs, without anti-HBc) was present in 533 patients (41.7%). Past HVC infection was found in 0.7 % (UC: anti-HCV 0.7%, CD anti-HCV 0.7%). Active hepatitis was not present in any patient. Neither anti-HBc patients without prophylactic treatment, nor AgHBs patients when immunosuppressive treatment was needed had a reactivation of their VHB infection. One patient was infected with HCV during immunosuppressive treatment, he was treated with antiviral treatment achieving sustained virological response. In multivariate analysis, older age was significantly related to HBV with a median age in positive anti-HBc patients of 43 (33–59) years compared with a median of 38 (28–52) in negative anti-HBc patients ( p = 0.002). In CD, neither localisation (L1, L2, L3) nor behaviour (B1, B2/B3) were related to HBV ( p = 0.421, p = 0.641 respectively). In UC, the extension of the disease was inversely related to HBV, so E1/E2 had significantly higher number of positive anti-HBc patients compared with E3 ( p = 0.004). Neither immunosuppressive treatment (tiopurinics and/or biological treatment) nor need of surgery were associated with HVB or HVC infection ( p = 0.753, p = 0.507, p = 0.092; p = 0.748, p = 0.669, p = 1.000, respectively). Conclusions: Prevalence of HBV in IBD patients (5.9%) is higher than the one reported in general population (1%) and similar to data reported in IBD patients. Conversely, HCV infection in this special population (0.7%) is lower than the one reported in general population (2.5%). Percentage of vaccination in this Spanish area is slightly low (41.7%) compared with the estimated percentage (59%).